Antigua and Barbuda : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation highlights that data for the first half of 2005 point to a widening fiscal deficit for Antigua and Barbuda. A combination of a reduction in capital spending and some improvement in revenues following a tightening of the concessions regime resulted in a closing of the primary deficit to 1 1\2 percent of GDP in 2004. Revenues have performed well following the reintroduction of the personal income tax. The external current account deficit has narrowed to about 11 percent of GDP, financed by foreign direct investment.